The tidal model : a guide for mental health professionals - Barker, Philip J. (Brunner-Routledge, 2005)
Based on extensive research, The Tidal Model charts the development of this model of care, outlining its theoretical basis and including clinical examples to show the benefits of encouraging the client's greater involvement in their treatment.